Big Tech's power, political corporate social responsibility and regulation. (June 2023) - Lindman, Juho; Makinen, Jukka; Kasanen, Eero
The economic dominance of large Internet tech companies, specifically the 'Big Five' (Google, Apple, Meta née Facebook, Amazon and Microsoft), is fundamentally complicating the organisation of society. Their positions raise profound questions, old and new, at the intersection of information systems and political philosophy, where companies have traditionally appeared in liberal democracies as economic operators rather than powerful political actors that threaten to limit citizens' fundamental rights significantly through their operations. Importantly, the traditional understanding of corporate social responsibility is rooted in the liberal-democratic conception of moral labour's division between public and private powers in a market economy. Focussing on this division, the paper analyses the various types of political power these companies wield and the complexities of regulating that power. Thus, it contributes to the IS discipline's theoretical discussion by introducing political theory concepts that hold untapped potential for reconciling Big Tech and modern liberal-democratic conceptions of society. Taking these concepts as underpinnings for discussing six types of power, in turn (business vs. politics, democratic government, institutions of a market economy, companies, civil society and citizens), the paper offers the discipline example research questions to tackle and points to potential directions for scholarship.